Identification of KCC2 Mutations in Human Epilepsy Suggests Strategies for Therapeutic Transporter Modulation - Duy, Phan Q.; David, Wyatt B.; Kahle, Kristopher T. (Frontiers in Cellular Neuroscience, 2019)
Epilepsy is a common neurological disorder characterized by recurrent and unprovoked seizures thought to arise from impaired balance between neuronal excitation and inhibition. Our understanding of neurophysiological mechanisms that render the brain epileptogenic remain incomplete, reflected by the lack of satisfactory treatments that can effectively prevent epileptic seizures without significant drug-related adverse effects. Type 2 K+-Cl- cotransporter (KCC2), encoded by SLC12A5, is important for chloride homeostasis and neuronal excitability. KCC2 dysfunction attenuates Cl- extrusion and impairs GABAergic inhibition, and can lead to neuronal hyperexcitability. Converging lines of evidence from human genetics have secured the link between KCC2 dysfunction and the development of epilepsy. Here, we review KCC2 mutations in human epilepsy and discuss potential therapeutic strategies based on the functional impact of these mutations. We suggest a strategy of augmenting KCC2 activity by antagonizing its critical inhibitory phosphorylation sites may be a particularly efficacious method of facilitating Cl- extrusion and restoring GABA inhibition to treat medication-refractory epilepsy and other seizure disorders.